Case Report: Short-Term Response to First-Line Crizotinib Monotherapy in a Metastatic Lung Adenocarcinoma Patient Harboring a Novel TPR-ROS1 Fusion - Wei, Shuli; Hu, Mangsha; Yang, Yan; Huang, Xiaojie; Li, Baizhou; Ding, Liren; Wang, Pingli (Frontiers in Oncology, 2022)
ROS1-rearranged patients account for 1-2% of non-small cell lung cancer (NSCLC) cases. Approximately 10 fusion partners have been discovered, while clinical practice is actively generating knowledge of new ones and their therapeutic responses. Herein, we report a patient with stage IV NSCLC that harbored a novel TPR-ROS1 fusion, which demonstrated a rapid but short partial response to first line crizotinib and primary resistance to subsequent ceritinib. Computed tomography detected a pulmonary nodule in a 53-year-old woman who presented with persistent cough. Histopathologic and molecular examination of the tissue biopsy indicated a poorly differentiated adenocarcinoma staining negative for PD-L1 but harbored a novel translocated promoter region (TPR)-ROS1 (T4:R35) gene fusion. Frontline crizotinib monotherapy elicited a rapid partial response after 1 month, although the disease progressed another 2 months later. After another 3 months of continued crizotinib treatment, the patient manifested newly emerged and enlarged lung and brain lesions. Genomic profiling still identified TPR-ROS1 as the only aberration, while a lymph node biopsy indicated PD-L1 immunopositivity. The patient was then treated with ceritinib and progressed within 1 month. She was started on chemotherapy with pemetrexed plus carboplatin and has achieved rapid partial response as of the latest follow-up. In summary, we provided clinical evidence of a novel TPR-ROS1 fusion and its roles as an oncogenic driver in metastatic NSCLC. To the best of our knowledge, ours is the first case to report this fusion in NSCLC. This case was characterized by a rapid yet short-term response to first line crizotinib and primary resistance to subsequent ceritinib, while no known genetic resistance mechanism was identified and other mechanisms including histologic transformation were unlikely. Future research is needed to unveil the resistance mechanism and formulate effective treatment strategies.